2019
DOI: 10.1177/1178223419879112
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Prognostic Factors of Survival in Breast Cancer Using a Frailty Model: A Multicenter Study

Abstract: Background: Using data from different health centers can provide more accurate knowledge of the survival prognostic factors and their effect on the patient’s survival. In this multicenter study, we aimed to investigate the role of prognostic factors on breast cancer survival with large data set. Methods: This historical cohort study was carried out using data from 1785 participants with breast cancer. Data were gathered from medical records of patients referring to 4 breast cancer research centers in Tehran, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
(52 reference statements)
1
10
1
Order By: Relevance
“…Breast cancer is one of the most common diseases among Iranian women. Oncological studies show that the prevalence of breast cancer among Iranian women is increasing, and the age of onset of this disease is decreasing with more disease intensity [ 8 , 16 ]. On the other hand, different factors influence the deterioration of the disease and its overall survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer is one of the most common diseases among Iranian women. Oncological studies show that the prevalence of breast cancer among Iranian women is increasing, and the age of onset of this disease is decreasing with more disease intensity [ 8 , 16 ]. On the other hand, different factors influence the deterioration of the disease and its overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, due to the population growth, the increase of life expectancy, the relative increase of old population, the annual increase of cancer and the acceleration of change among influential factors in the escalation of cancer prevalence such as the prevalence and the development of the cancer risk factors, the rate of cancer development is predicted to rise and it will be doubled during the next two decades [ 8 , 16 ]. Therefore, this disease and programs to control are of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…Our results revealed no significant relationship between diagnosis age and breast cancer patients' survival rate or cure probability. However, some studies have reported significant association [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Cox method models the hazard ratio rather than the survival time directly, and the complexity of the hazard ratio estimate interpretation is considered as a major problem. 4 , 11 The censored quantile regression (CQR) model seeks to model the survival time separately for each given quantile directly, and investigates the covariate effects in different quantiles. In this model, the covariate effects can be changed for patients with different risks and is a flexible model for controlling the heterogeneity of covariate effects.…”
Section: Introductionmentioning
confidence: 99%
“…That is at least 10 years lower than the world. 4 A major factor in reducing the survival of breast cancer patients is recurrence. 5 Cancer may come back in the same place as original cancer (local recurrence), or it may spread to other areas of your body (distant metastases).…”
Section: Introductionmentioning
confidence: 99%